근치적자궁절제술을 받은 자궁경부암 여성의 배뇨장애 빈도, 강도 및 일상생활 불편감 - 전나미; 노기옥; 송현주; 김상희; Chun, Nami; Noh, Gie Ok; Song, Hyun Ju; Kim, Sang Hee (Journal of Korean Academy of Nursing, 2016)
Purpose: This study was done to identify frequency, intensity of urinary dysfunction and daily life distress in women after a radical hysterectomy for cervical cancer. Methods: One hundred and fifty seven women who had undergone a radical hysterectomy and one hundred and sixty five women as healthy controls completed questionnaires on intensity of urinary dysfunction and daily life distress caused by urinary dysfunction. Results: Women with cervical cancer showed higher frequency of urinary dysfunction than healthy controls. Major urinary dysfunction for women with cervical cancer in order of frequency were night-time incontinence (odds ratio=10.39, p<.001), difficulty in starting urination, weak urine stream and sense of incomplete emptying of bladder. The highest score on intensity was difficulty in starting urination, followed by urgency, weak urine stream, daytime frequency and sense of incomplete emptying. Night-time incontinence was the urinary symptom causing the most daily life distress for cervical cancer women followed by difficulty in starting urination, urgency, sense of incomplete emptying, and night-time frequency. Conclusion: Results suggest that nurses should address the potential postoperative urinary complications and develop long term interventions to decrease urinary dysfunction and daily life distress for women who have had a radical hysterectomy for cervical cancer.